Coronary plaque characteristics quantified by artificial intelligence-enabled plaque analysis: Insights from a multi-ethnic asymptomatic US population - Guadalupe Flores Tomasino; Caroline Park; Kajetan Grodecki; Jolien Geers; Donghee Han; Andrew Lin; Keiichiro Kuronuma; Nipun Manral; Emily Xing; Heidi Gransar; Sebastien Cadet; Alan Rozanski; et al. (American Journal of Preventive Cardiology)
Background: Ethnic differences in coronary atherosclerosis remain to be fully elucidated. We aimed to assess quantitative plaque characteristics from coronary CT Angiography (CCTA) in relation to ethnicity and cardiovascular risk factors in a multi-ethnic asymptomatic US population. Methods: This cross-sectional study retrospectively evaluated 388 asymptomatic patients selected from a prospective CCTA registry. A total of 194 patients from ethnic minority groups (Asian, African American, and Hispanic) were matched by age, sex, and cardiovascular risk factors to 194 White patients. Quantitative plaque volumes—including total plaque, non-calcified plaque, low-attenuation non-calcified plaque (<30 Hounsfield Units [HU]), and calcified plaque—were measured using artificial intelligence-enabled software. Pericoronary adipose tissue attenuation (PCAT) was also assessed and reported in Hounsfield Units (HU). Results: The total study population included 388 patients (age 59.9±11.7 years, 68% male), of which 63% had coronary atherosclerosis with total plaque volumes of 149[IQR 50-438] mm3, driven predominantly by non-calcified plaque (122, IQR 27-369) mm3. Men presented higher volumes of all plaque components compared to women (P<0.05). In multivariable analysis adjusted for cardiovascular risk factors, only African American patients were associated with lower total plaque (β=-89.2, P=0.036), calcified (β=-26.1, P=0.015), and non-calcified plaque volumes (β=-62.7, P=0.022). African American patients were also associated with higher PCAT (β=5.8, P<0.001), along with family history of coronary artery disease (β=2.1, P=0.04). Conclusions: Our study showed a uniformly high prevalence of atherosclerosis in this asymptomatic cohort, with lower plaque volumes of all sub-components in women. African American patients were associated with lower quantitative plaque volumes (total, non-calcified and calcified) but with higher PCAT compared to White patients; with no significant differences observed among other ethnic minorities.